Level of sodium chloride (NaCl) and profile of cervical mucus of dairy cattle at various age synchronized by prostaglandine - Ondho, Y. S.; Akbar, F. A.; Lestari, D. A.; Samsudewa, D. (Diponegoro University, 2019)
Objectives of this study were to compare the percentage of Sodium Chloride (NaCl) and cervical mucus profile which includes potential of Hydrogen (pH), abundance of cervical mucus, spinnbarkeit and ferning of dairy cattle at different age during estrus cycle. Thirty Two head of dairy cattle were used as materials which are 2 years old (n = 2), 3 years old (n = 18), 4 years old (n = 8) and 5 years old (n=4). Dairy cattle were estrus synchronized using 50 mg/head of prostaglandin. Data was collected on 48, 72, 78, 84, 90, 120, 144 and 408 hours after prostaglandin administration. The data were analyzed by using non parametric statistic which was Kruskal-Wallis H test. The significant data was tested with Mann-Whitney U test. The result showed that the abundance of cervical mucus was significantly different (P<0.05; χ2 = 0.011) on 84 hours after estrus synchronization. However, level of NaCl, abundance, spinnbarkeit and ferning of cervical mucus was not sigificantly different. In conclusion, the age of dairy cattle did not affected to the condition NaCl percentage, spinnbarkeit, pH and ferning of cervical mucus, but affected to the abundance of cervical mucus on 84 hours after adminitration of prostaglandine.